Classroom Techniques Used In Vocabulary DevelopmentActivities In English Classroom: A Naturalistic Study AtMts Negeri Surakarta 2 In 2015/2016 Academic Year - Astutik, Puji, Prof. Dr. Endang Fauziati, M. Hum, Dr. Anam Sutopo, M. Hum (2016)
This study is carried out to describe classroom techniques used in vocabulary activities in English classroom at MTs Negeri Surakarta 2. The aims of this research are: (1) to describe the kinds of classroom techniques used in vocabulary activities, (2) the purpose of using each classroom technique, (3) the teacher's roles, (4) the student's roles, and (5) instructional materials used by the English teachers at MTs Negeri Surakarta 2. The kind of this research is descriptive qualitative research especially naturalistic study in analyzing the data. The methods of collecting data in this research are observation, interview and document. The finding of the study shows that there are some classroom techniques used by English teachers at MTs Negeri Surakarta 2 such as: memorization (vocabulary card system), synonym, selfdefining context, picture and drawing, antonym, and reading aloud. The teacher have roles as model, instructor, consultant, group organizer, evaluator, and facilitator. The student have roles as participant, demonstrate their knowledge and understanding, engage actively in learning, dialog and interaction with teacher, learner member group and learn by interacting with other, tutor for other learner, and shows respect. There are some materials used by English teachers, such as textbook, work book, dictionary, photocopy exercises, and powerpoint on LCD. The conclusion of this research is that English teacher at MTs Negeri Surakarta 2 used various classroom techniques which can improve the students' ability. Various techniques can make the student interested in English teaching-learning process. It does not make the class monotonous. The students become more active and creative. Based on the result, apparently, classroom techniques used by the teacher have important role in the teaching-learning process.